HUBUNGAN KARAKTER LAYANAN PERAWAT TERHADAP KEPUASAN PASIEN DI RUMAH SAKIT UMUM DAERAH KABUPATEN CILACAP - Wahidin, Yuli Astuti Andriyatin; Ana Trisnawati Wimbagya (Jurnal Ilmiah Keperawatan, 2022)
Background: Along with technological advances in the field of nursing education, the community, clients and clients' families in particular have very high hopes for hospitals to cure their illnesses. The quality of nursing services in a hospital will greatly affect the level of satisfaction of clients and their families. However, currently nursing services in post-pandemic patients are experiencing many obstacles, mainly due to the number of nurses and increasing number of Covid-19 patients. Objective: To determine the relationship between the character of nurse services and patient satisfaction at the Cilacap Regency General Hospital . Method: The method used in this study is descriptive correlation. A sample of 30 inpatients was taken by simple random sampling. The research instrument used a questionnaire related to service characteristics and patient satisfaction. Results: The results showed that the responsiveness (responsiveness) of nurse services was good (70%), and 100% stated good reliability and empathy. As for the character of nurse services in terms of Assurance (trust), most of them are good (93.3%), and Tangible is mostly good, 29 respondents (96.7%). The level of satisfaction is mostly high (60%). The test results using chi square obtained a p value of 0.000 with (p <0.05) and an X² value of 23.077. Conclusion: There is a relationship between the character of nurse service and patient satisfaction at Cilacap District Hospital.